SDG2 Zero Hunger: What Should We Do To Achieve The Goal? - Ahmed, Akhter; Tauseef, Salauddin (2018)
Using two survey rounds of IFPRI's Bangladesh Integrated Household Survey (BIHS), IFPRI researchers under the Bangladesh Policy Research and Strategy Support Program (PRSSP) analyze trends in hunger from 2011/12 and 2015, as well as offer policy options for accelerating reductions in hunger and undernutrition.